The problem of using legal terminology in the modern civil procedural legislation - Ilyassova, G.A.; Assetova, G.B. (Bulletin of the Karaganda University “Law Series”, 2021)
The article analyzes the results of a linguistic examination of legal terminology, which is used in the text of the Civil Procedure Code of the Republic of Kazakhstan in the state language, which was adopted in 2015. The purpose of the study is to ensure the safety of the authenticity of the texts of the civil procedure legislation in the state and Russian languages, as well as the unification of legal terms in the Kazakh language. Due to the fact that the language of the law is the official language, this issue must be approached with the utmost seriousness. The authors, in the process of analyzing individual articles of the Civil Procedure Code, found such errors as incorrect translation of legal norms from Russian into Kazakh, as well as meaningless translation, translation of one term in several versions. So, the authors offer their correct translation, justify each translation separately. The ambiguity of the texts of laws in the Kazakh language, incorrect translation of terms are explained by the fact that bills are first developed in Russian, and then hastily translated into the state language. It is known that not qualified lawyers are involved in translating laws; translators are involved in this process. In conclusion, the authors substantiate the need to improve the status of the state language, the adoption of laws in the state language, the involvement of qualified lawyers-professionals who are fluent in the state language in lawmaking